Integrating Indigenous Cultural Values into Character Education: An Implementation Model for Elementary Schools - Steti Jelita; Hafiz Hidayat; Ismira Ismira (Journal of Education Research, 2026)
The erosion of local cultural values in contemporary society has raised serious concerns about the moral and character development of young learners in Indonesia. This study aimed to investigate the implementation of Serayo local wisdom as a strategy for strengthening student character at SDN 113/III Sako Dua. A descriptive qualitative approach was employed, with teachers and students serving as research informants. Data were gathered through observation, in-depth interviews, and documentation, and subsequently analyzed using the Miles, Huberman, and Saldana interactive model. The findings revealed that Serayo local wisdom values—encompassing mutual cooperation, respect for elders, social solidarity, and environmental stewardship—were systematically integrated into classroom learning, school culture, and daily routines. These practices demonstrably reinforced students' honesty, responsibility, and social sensitivity. The study concludes that culturally rooted instructional approaches serve as an effective and sustainable foundation for character education in elementary schools. These findings imply that local wisdom-based learning models can be systematically developed and replicated across diverse cultural contexts in Indonesia, offering a practical framework for educators and policymakers seeking culturally responsive approaches to character education.